Spanning silos : the new CMO imperative - Aaker, David A. (Boston, Mass. : Harvard Business School Press, 2008)
'Spanning Silos' explains how to strengthen your credibility with silo teams and your CEO, use cross-functional teams and other strategic linking devices, foster communication across silos, develop common planning processes, and adapt your brand strategy to silo units.
Introduction: The new CMO -- why? -- Find the right role and scope: the CMO's new job description -- Gain credibility and buy-in -- Use teams and other routes to silo linking -- Develop a common planning process and information system -- Adapt the master brand to silo markets -- Prioritize brands in the portfolio -- Create winning marketing in a silo world -- Conclusion: The CMO's first ninety days.
Includes bibliographical references (pages 207-209) and index.
Description based on print version record.
Keywords: Marketing -- Management; Marketing; Management; Marketing -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books